Recurrent ectopic pregnancy after ipsilateral salpingectomy: a rare case report - Yadav, Amita; Gupta, Veena; Patel, Shweta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Ectopic pregnancy occurs in 1.3% to 2% of all pregnancies, and there is a potential threat for maternal morbidity and mortality. Ipsilateral ectopic pregnancy after partial or total salpingectomy is a rare occurrence. Current surgical management of tubal pregnancy includes conservative (usually salpingostomy) and radical (total or partial salpingectomy) methods. However, in some cases, these methods may not solve the problem. We are presenting the case of a 26 year old female G3P1+1 who presented with bleeding per vaginum, pain in abdomen, severe pallor, hypotension, and tachycardia following 3 months amenorrhoea. She had a previous right sided ruptured ectopic pregnancy and right salpingectomy done 5 years back. On laparotomy, there was right adnexal mass of 5x7 cm size. Given the possibility of transperitonal migration of human embryos and sperm, which has a greatly increased risk associated with previous ectopic pregnancies, total salpingectomy should be the treatment of choice if conservative methods of treatment are not suitable. This case emphasizes that salpingectomy does not exclude ectopic pregnancy on the ipsilateral side. Total salpingectomy too carries the potential for the recurrence of ectopic pregnancy on the same side hence the need for clinician awareness and vigilance.